2020
DOI: 10.1097/sih.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emotional Response on the Performance of a Simulated Laparoscopic Task

Abstract: Introduction: An emotional state impacts task performance and cognition. However, evidence of the effect of an induced emotional state on laparoscopic performance has not yet been documented. We investigated whether surgical residents in whom a positive emotion had been induced would produce a better laparoscopic task performance than residents in whom a negative emotional state had been induced. Methods: This controlled laboratory study recruited a total of 53 junior surgical residents who were divided into 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The study sample size (number of teams) was determined according to a similar investigation. In 2020, Yang et al reported the effect of different emotions on laparoscopic performance [ 16 ]. They asked surgeons-in-training to perform simulated surgical tasks on the Lap Mentor (Simbionix, Tel Aviv, Israel) immediately after watching three movies that evoked different emotions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study sample size (number of teams) was determined according to a similar investigation. In 2020, Yang et al reported the effect of different emotions on laparoscopic performance [ 16 ]. They asked surgeons-in-training to perform simulated surgical tasks on the Lap Mentor (Simbionix, Tel Aviv, Israel) immediately after watching three movies that evoked different emotions.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical dexterity deteriorated in a noisy environment [ 14 , 15 ]. Negative emotions triggered by a noisy environment has led to a deterioration in the cognitive ability of surgeons due to deteriorated working memory and to interference in the decision-making process [ 16 , 17 ]. People in noisy environments reported difficulty in maintaining focus, thus showing reduced ability in assessing a situation and a tendency for selecting high-risk strategies for resolving a problem without being fully aware of the consequences [ 8 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation